Kakovost življenja starostnikov z depresijo v domskem varstvu - Pap, Zoltan (Obzornik zdravstvene nege, 2015)
Introduction: The period of old age is accompanied with many changes which increase the vulnerability of elderly people, bring about typical symptoms of depression and influence the quality of life. The main purpose of this research is to identify the difference in the quality of life, inclusion in social activities and self-assessed health status of the elderly with and without depression. Methods: Quantitative methodology was used in this research. It included 138 participants, 69 of which suffered from depression and 69 did not suffer from depression. Data were collected through personal interviews with the elderly who were residents of nursing homes for the elderly in the Pomurje region. Interviews were conducted with the help of EuroQol-5D (Euro Quality of Life - 5 Dimension) questionnaire. The reliability coefficient was good (r = 0.86). Research work was conducted in October 2013. Data analysis was performed using a IBM SPSS Statistics ver. 19.0 statistical programme. For hypothesis testing Hi-square test was used. Results: The results show that the quality of life of the respondents with depression was significantly poorer (p < 0.001) than the quality of life of those without depression disorder. Respondents with depression are significantly less involved (p < 0.005) in social activities than those without depression disorder. Self-assessed health status grade of respondents with depression is also significantly worse (p < 0.001). The results are shown with visual-analogue scale. Discussion and conclusion: Depression causes severe deterioration in quality of life of individuals suffering from it. The elderly with depression disorder, living in nursing homes for the elderly, more often exclude themselves from the activities, which they are physically capable of performing and they are less willing to join social activities. More emphasis should be placed to retain the existing skills of the elderly and thus their feeling of self-efficiency and satisfaction would be preserved.
Keywords: duševno zdravje; elderly; health status; kvaliteta življenja; mental health; nursing homes; samoocena; social inclusion; socialna vključenost; starostniki; zdravje